Heterogeneidade de conhecimento de língua inglesa no ensino médio em uma escola pública federal - Souza, Lídia Bravo de (2008)
This dissertation has the main purpose to describe and interpret, under the hermeneutic phenomenological approach, the experience of multilevel knowledge English language classes lived by first year Senior High School teachers and students in a federal institution. It is based on the theoretical postmodern social and cultural history principles having Vygotsky (1929/2001,1935/2003) and Bakhtin (1929/2004) as main postmodern theorists. In considering the social function of teaching English as a second language at public schools, this study is based on Celani (2002,2003,2004) and Moita Lopes (1996,1999,2001,2002,2003,2006). In order to understand the repercussions of culture and exclusion in the school context, this study is based on Sacristán (2002); and also on Souza-e-Silva (2003/2004) and Amigues (2004) to understand the institutional normative prescriptions that influence the teacher s job. Finally, it is supported by Fidalgo (2002), Rabelo (2004) and Zabala (1998) for fundamentals of evaluation in the school context. The data were collected throughout the school year of 2006, during and after English language classes of two different teachers. The participants included one pedagogical assistant, two English language teachers and seventy-one first year Senior High School students. The data included : (a) the transcriptions of audio recordings of semi-structured interviews with the teachers and the pedagogical assistant; (b) open-ended questions sent by e-mail messages to the participant teachers; (c) 18 audio-recorded classes; (d) two open-ended questionnaires answered by the participant students; (e) field notes and class observation notes. Data analysis is based on the thematization recommended by van Manen (1990), and its systematized procedures by Freire (2007). The themes emerged from the thematization were perceived as a universe in three dimensions: the institutional dimension and its prescriptions; the teaching dimension considering the challenges of the teacher as a mediator; and the students´ dimension, in their interactions with the teacher and with other students